Spirituality according to Paul imitating the apostle of Christ - Reeves, Rodney, 1957- (Downers Grove, Ill. : InterVarsity Press, 2011)
"Spirituality often evokes images of quiet centeredness, meditative serenity and freedom from life's pressures. Contrast Paul, who promotes a cross-shaped spirituality for fools making their way through life's trials. The brand images are crucifixion, burial and resurrection--surely a counterintuitive marketing program for living spiritually!"--From publisher description.
Crucified with Christ. Foolish death : suffering the loss of all things ; Living sacrifice : crucifying the world ; Holy template : denying the flesh ; Free slaves : graceful obedience -- Buried with Christ. Whole body : one faith ; Common bonds : worship as corporate reality ; Sacred community : sex and marriage ; Generous fellowship : work and money -- Raised with Christ. Bold confession : wasting no time ; Blessed hope : the wait/weight of glory ; Putting up a fight : opposing the powers ; Seeing things : mystical journeys ; Conclusion : the imitable life.
Includes bibliographical references (p. [237]-241) and indexes.
Description based on print version record.
Keywords: Christian life; Spirituality; Paul, -- the Apostle, Saint; Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Jesus Christ -- Example; RELIGION / Christian Life / General; Electronic books